Fatores de virulência e infecção epitelial in vitro de biofilmes simples e mistos de Cndida albicans, Staphylococcus aureus sensível (MSSA) e resistente à meticilina (MRSA) - Zago, Chaiene Evelin [UNESP] (2015)
The aim of this study was to evaluate, in vitro, the interaction between C. albicans and methicillinsusceptible (MSSA) and resistant (MRSA) S. aureus in relation to some of their major virulence factors. These factors were analyzed considering the three microorganisms in single and dual cultures. The interaction between these microorganisms was evaluated by counting colony-forming units (CFU/mL), analysis of metabolic activity by the XTT assay and quantification of the total biomass by crystal violet dye at 90 minutes, 12, 24, and 48 hours. To analyze the production of proteinase (SAP) and phospholipase (PL-C), fluorometric kits were used. The structure of the biofilms was acessed by scanning electron microscopy (SEM). Further, single and dual cultures of microorganisms were used to infect a reconstituted human oral epithelium (RHOE). The pattern of colonization and invasion of the RHOE was evaluated after 24 hours using the in situ hybridization technique (PNA-FISH). The damage caused by microorganisms in the tissue was evaluated by quantification of the lactate dehydrogenase enzyme (LDH) released. Molecular techniques (RT-qPCR) were also used to quantify the number of microorganisms colonizing the epithelium and to evaluate the expression of virulence genes. Gene expression was evaluated in biotic (RHOE) and abiotic (24-well polystyrene microplate) surfaces for single and dual cultures. The results from quantification assays were compared using two-way ANOVA with Tukey post-hoc test, while data from enzymatic activities were analyzed by one-way Welch-ANOVA followed by Games-Howell post hoc test. The results of gene expression were analyzed by one-way ANOVA with Tukey for data satisfying the assumptions of normality and homoscedasticity or one-way Welch-ANOVA followed by Games-Howell for heteroscedastic data. LDH results were also...(Complete abstract electronic access below)